Perinatal risk factors for mortality in very preterm infants—A nationwide, population‐based discriminant analysis. (14th April 2022) - Norman, Mikael; Nilsson, David; Trygg, Johan; Håkansson, Stellan
Abstract: Aim: To assess the strength of associations between interrelated perinatal risk factors and mortality in very preterm infants. Methods: Information on all live‐born infants delivered in Sweden at 22–31 weeks of gestational age (GA) from 2011 to 2019 was gathered from the Swedish Neonatal Quality Register, excluding infants with major malformations or not resuscitated because of anticipated poor prognosis. Twenty‐seven perinatal risk factors available at birth were exposures and in‐hospital mortality outcome. Orthogonal partial least squares discriminant analysis was applied to assess proximity between individual risk factors and mortality, and receiver operating characteristic (ROC) curves were used to estimate discriminant ability. Results: In total, 638 of 8, 396 (7.6%) infants died. Thirteen risk factors discriminated reduced mortality; the most important were higher Apgar scores at 5 and 10 min, GA and birthweight. Restricting the analysis to preterm infants <28 weeks' GA ( n =  2939, 16.9% mortality) added antenatal corticosteroid therapy as significantly associated with lower mortality. The area under the ROC curve (the C‐statistic) using all risk factors was 0.86, as determined after both internal and external validation. Conclusion: Apgar scores, gestational age and birthweight show stronger associations with mortality in very preterm infants than several other perinatal risk factors available at birth.